Distribution of Feeding Styles after Pyloromyotomy among Pediatric Surgical Training Programs in North America - Juang, David; Adibe, Obinna O.; Laituri, Carrie A.; Ostlie, Daniel J.; Holcomb, George W., III; Peter, Shawn D. St. (European Journal of Pediatric Surgery, 2012)
Introduction The feeding regimen employed after pyloromyotomy for pyloric stenosis continues to be a topic of debate and has yet to be evaluated in a prospective, randomized trial. To understand the spectrum of current feeding schedules being utilized in the various training programs, we queried the program directors or representatives about their feeding schedules.Methods Through the use of multiple electronic communication resources, we surveyed 47 pediatric training programs in the United States and Canada about their postpyloromyotomy feeding schedules. Questions included time to first feed, how the schedule is advanced, and criteria for stopping feeds and discharge.Results Reponses were received from 34 of the 47 institutions. Six programs had variable times of delay before instituting feeding whether ad libitum (ad lib) or protocol. The average time of delay was 4.3 hours. Six programs reported both ad lib feed and protocol feeding regiments. Twelve institutions used ad lib feeding regiments. Eight started feeding without delay. Twenty-six programs including our institution currently employ a protocol-based feeding regiment. Of these programs, seven begin the protocol without delay.Conclusions Despite retrospective evidence in support of ad lib feeds after pyloromyotomy, the majority of teaching institutions employs protocols for the postpyloromyotomy feeding schedule. There is clearly a role for a prospective, randomized trial to compare ad lib to schedule feeding.
Keywords: pyloric stenosis; feeding regimen; ad libitum feeds; pyloromyotomy